Economics for Today's World - Tucker, Irvin B. (Cengage Learning, Inc, 2007)
Straightforward and engaging, "Economics for Today", 5e uses a unique textual and visual learning system to present, reinforce and test students comprehension while teaching them the basic concepts of economic principles while also giving them the context to apply them in their everyday lives. This concise text focuses on core concepts, providing an extremely student friendly text that includes unparalleled pedagogy and teaching support. The new edition also includes ThomsonNOW, a powerhouse of online resources including custom designed learning paths for each student, lively videos, interactive assessments, testing tools, and much more. Engaging and easy to use, this book's fast-paced, action-packed approach explains all the essential concepts without being encyclopedic as it teaches students to apply basic economic principles to real-world issues